2010
DOI: 10.1089/ten.tea.2009.0051
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEnhancement of SAOS-2 Cell Calcified Matrix Deposition onto Radio Frequency Magnetron Sputtered Bioglass-Coated Titanium Scaffolds

Abstract: In bone tissue engineering, bioglass coating of titanium (Ti) scaffolds has drawn attention as a method to improve osteointegration and implant fixation. In this in vitro study, bioactive glass layers with an approximate thickness of 1 microm were deposited at 200 degrees C onto a three-dimensional Ti-6Al-4V scaffold using a radio frequency (r.f.) magnetron sputtering system. After incubation with SAOS-2 human osteoblasts, in comparison with the uncoated scaffolds, the bioglass-coated scaffolds showed a twofol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 71 publications
0
69
0
Order By: Relevance
“…The cells were cultured in McCoy's 5A modified medium with L-glutamine and HEPES (Cambrex Bio Science, Baltimore, MD, USA), supplemented with 15% foetal bovine serum, 2% sodium pyruvate, 1% antibiotics, 10 -8 M dexamethasone, and 10 mM β-glycerophosphate (Sigma-Aldrich, St. Louis, MO, USA) (Saino et al, 2010). The osteogenic factor β-glycerophosphate was used at 10 mM concentration as previously reported in the literature (Rao et al, 2003;Gartland et al, 2005).…”
Section: In Vitro Cell Assays Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were cultured in McCoy's 5A modified medium with L-glutamine and HEPES (Cambrex Bio Science, Baltimore, MD, USA), supplemented with 15% foetal bovine serum, 2% sodium pyruvate, 1% antibiotics, 10 -8 M dexamethasone, and 10 mM β-glycerophosphate (Sigma-Aldrich, St. Louis, MO, USA) (Saino et al, 2010). The osteogenic factor β-glycerophosphate was used at 10 mM concentration as previously reported in the literature (Rao et al, 2003;Gartland et al, 2005).…”
Section: In Vitro Cell Assays Cellsmentioning
confidence: 99%
“…The samples were kept in 100% ethanol for 15 min, and then critical point-dried with CO 2 . The specimens were sputter coated with gold and observed at 250x and 1500x magnification respectively with a Leica Cambridge Stereoscan 440 microscope (Leica Microsystems, Bensheim, Germany) at 8 kV (Saino et al, 2010).…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration curves to measure the extracted proteins were performed by an ELISA assay (24,34). The results are expressed as fg/(cell xscaffold).…”
Section: Extraction Ofthe Bone Matrixmentioning
confidence: 99%
“…Bioactive glass and nanohydroxyapatite (BG-nHA) on titanium-alloy orthopaedic implants and surrounding bone tissue in vivo was evaluated and observed that these coatings could enhance the osteointegration of orthopaedic implant (Xie et al, 2010). Bioglass coating of the three-dimensional Ti scaffolds by the radio frequency magnetron sputtering technique determines an in vitro increase of the bone matrix elaboration and may potentially have a clinical benefit (Saino et al, 2010). Biocompatible yttrium-stabilized zirconia (YSZ) in the form of nanoparticles and bioactive Bioglass (45S5) in the form of microparticles were used to coat Ti6Al4V substrates by electrophoretic deposition with potential applications in the orthopedics (Radice et al, 2007).…”
Section: Bioglass As Coating Of Implantsmentioning
confidence: 99%